Dynamic output-feedback controllers for discrete-time linear systems with markovian jumping parameters, imperfect mode observation and additive noise perturbations - Mercado, Pablo Ivan Zamora (2020)
A class of stationary dynamic output-feedback controllers for discrete-time Markovian Jumping Linear Systems(MJLS) considering the minimization of a long run average cost is studied. The Markov chain that governs the parameters is not required to be ergodic, and it is allowed to be periodic and contain transient states / non-communicating classes, which enlarges the class of system, e.g. now comprising periodic systems as a sub-class. A compact optmization formulation is obtained for the mode-independent/detector-based controller of partial/full order, allowing one to explore the complexity and consequently obtain the best implementable performance for an application. We develop a two stage feasibility - optimization algorithm using the operator-based approach. We present a set of numerical examples in the context of random non-trivial systems that are subject to jumps in order to represent our results and compare the performance with a classical genetic algorithm, resulting in a clear advantage for our proposed algorithm.